New record of Eupteryx decemnotata (Hemiptera: Cicadellidae) in Argentina. Biological traits and description of the female and its immature stages - Pereyra, Mora (2025)
During a survey of leafhoppers (Hemiptera: Cicadellidae) associated with aromatic crops, the Ligurian leafhopper, Eupteryx decemnotata Rey was identified for the first time in the Platense Horticultural Belt in Buenos Aires province, Argentina. This study provides a detailed description of the female genitalia and immature stages, along with biological traits, including developmental time from egg to adult, sex ratio, oviposition sites preference and host plants. This leafhopper was reported on oregano, thyme, rosemary and mint plants. Significant damage to host plants was observed due to feeding activity, with females showing a marked preference for ovipositing in secondary veins of leaves (31.15%), followed by stems (21.31%) and main veins (19.67%). The total developmental time from egg to adult averaged 29.14 days under controlled conditions, with the fifth instar being the longest. The sex ratio was male-biased (59.49% males, 40.51% females). This study expands the known distribution of E. decemnotata and provides essential biological and morphological data that contribute to its taxonomic identification and pest management strategies.